Analisis Manajemen Pembelajaran Online Berbasis Media Sosial WhatsApp untuk Meningkatkan Motivasi dan Hasil Belajar Siswa Materi Sistem Pencernaan - Mieke Nurhayati; Dakir dakir; Noor Hujjatusnaini (Universitas Lampung, 2021)
This research is a quantitative descriptive study. The research sample were 58 students at SMPN-1 Mentaya Hilir Utara, Kotawaringin Timur Regency. The learning management instrument used an assessment questionnaire for planning, organizing, implementing, and evaluating learning which was assessed by 4 observers. learning outcomes were analyzed using classical assumption tests consisting of normality tests and homogeneity tests, as well as hypothesis testing using the Paired sample T test and Independent sample T test. The results of the study found that the management of online learning based on whatsApp social media was carried out